Heterologous expression, biochemical characterisation and computational analysis of Bacteroides fragilis enolase. (June 2022) - Ugurel, Erennur; Kocer, Sinem; Sariyer, Emrah; Mutlu, Ozal; Inci, Tugba Gul; Ugurel, Osman Mutluhan; Turgut-Balik, Dilek
Abstract: Bacteriodes fragilis is an anaerobic bacterium found in the human intestinal flora. In this study, Bf Eno was targeted with a structure-based drug design approach because inhibition of this enzyme may prevent both the aerobic and anaerobic pathways due to its role in the glycolytic pathway. First, the gene encoding Bf Eno was cloned, expressed and the protein produced over 95% purity. The Km and Vmax values of Bf Eno were determined as 314.9 µM and 256.2 µmol/min.mg, respectively. Drug-like chemicals were retrieved from the ZINC database for high-throughput virtual screening analyses. As a result of screening study, the ZINC91441604 has been proposed to bind to the active site of the enzyme and remain stable. The same compound exhibited weak binding to the human enolases than the bacterial enolase. Hence, ZINC91441604 may be proposed as a novel candidate for further in vitro and in vivo drug analysis towards the treatment of B. fragilis infections. Graphical Abstract: ga1 Highlights: Bacteroides fragilis has been developing drug resistance. B. fragilis enolase was cloned, expressed and obtained with over 95% purity. Km and Vmax values of Bf Eno were determined as 314.9 µM and 256.2 µmol/min.mg, respectively. Potential inhibitors were identified using docking and MD simulation analyses.